The 2CHANCE model: Α proposal for scientific literacy in second chance schools and a supplementary case study upon a ‘dilemma’ in prison education - Tzampazi, Anna; Seroglou, Fanny (Adult Education Critical Issues, 2023)
In this paper we present a methodological implement for science teaching in a particular part of adult education, the Second Chance Schools. The resulting model is called 2CHANCE and has been developed to facilitate pre- and in-service adult educators in their science education work that creates the framework for adult learners’ scientific literacy and the conditions for transformative learning aiming at learners' participation in socio-political becoming and cultivation of critical thinking and awareness. It is a structured framework that (a) supports the selection of educational topics during the scheduling of a science course (b) assists the development of teaching activities for scientific literacy and (c) provides criteria for the evaluation of the teaching implementations.In addition, we present a supplementary case study on a ‘dilemma’ in prison education as an example of using the model.